ответ:б) -32+(78-9)=37
1) 78-9=69
2)-32+69=69-32=37
г) -63-(-63+1)=-1
1) -63+1=-62
2) -63-(-62)=-63+62=-1
е) (37-49)-(87-59)=-40
1) 37-49=-12
2) 87-59=28
3) -12-28=-40
з) -(-35+2)+(-35-8)=-10
1) -35+2=-33
2) -35-8=-43
3) -(-33)+(-43)=-10
Пошаговое объяснение:
ответ:б) -32+(78-9)=37
1) 78-9=69
2)-32+69=69-32=37
г) -63-(-63+1)=-1
1) -63+1=-62
2) -63-(-62)=-63+62=-1
е) (37-49)-(87-59)=-40
1) 37-49=-12
2) 87-59=28
3) -12-28=-40
з) -(-35+2)+(-35-8)=-10
1) -35+2=-33
2) -35-8=-43
3) -(-33)+(-43)=-10
Пошаговое объяснение: